The Reflection on Sheikh Reza Talabani’s Visual Innovations - Ali, Adnan Ahmed; Fazilat, Mahmud (Al-Adab Journal, 2022)
Sheikh Reza Tallabani, the renowned Kurdish poet of classical style, is an unrivaled poet of satire poetry. He has composed Kurdish, Persian, Arabic, and Turkish poems, demonstrating immense mastery in each language. His poems are flawless in all aspects. Despite his vast mastery of the literature of the ethnicities and nations of the region and his familiarity with poets’ Divans, he created his unique style instead of following the lead of other poets. Being a gifted poet, Sheikh Reza was dexterous in linking objects to sensory and abstract phenomena to form imaginary images. As an essential component of poetry to connect mental concepts with external phenomena and objects exterior to the mind, figures of speech play a crucial role. As a means of communication, language becomes intertwined with figures of speech in literature. Figures of speech and poetic images constitute its subject. Seeking to ascertain the effect of geography, nature, and conventions on the formation of imaginary images and evaluate the innovation of Sheikh Reza in the Divan of Persian and Kurdish poetry based on the constitutive elements, the author investigates the figures of speech. The article divides these images into three categories: clichéd images, innovations in clichéd images, and innovation in creating images in similes and metaphors. It then compares them with a sample of poems by Persian classical poets.